Occupational Hazards in the Chemical Industry: Scoping the Relevance for Prevention of Health Hazards - Salvi, Jayashree (Innovational: Journal of Nursing and Healthcare, 2024)
Occupational illnesses and hazards are still mostly unexplored topics in global literature. A subcategory of occupational hazards called “chemical hazards” involves a range of chemicals. Chemical exposure at work can have negative short-term or long-term impacts on health. The majority of sites include a variety of chemical substances in gaseous, liquid, or solid form. These toxins can enter an unprotected body through being ingested, absorbed through the skin, inhaled, injected, or punctured. The primary duty of anyone managing a business or undertaking, according to the Work Health and Safety Act, is to ensure that work being done as part of managing the business or undertaking does not risk the health and safety of employees and other people. The exposure of workers to risks at work must be kept to a minimum to safeguard them. The hierarchy of controls can be used to decide which actions will best reduce exposures. The hierarchy of controls consists of five tiers of measures taken to reduce or eliminate risks. According to general effectiveness, elimination, substitution, engineering controls, administrative controls, and personal protective equipment are the chosen order of action. Reducing worker exposures and the risk of disease or injury can be accomplished using this hierarchy. We learned from our review that India has a significant occupational health concern. It has a direct and indirect impact on the workers’ physical, physiological, and mental wellbeing. In addition, there is an issue with industrial workers’ lack of awareness of occupational dangers and preventative actions.